Continued use of afatinib with the addition of cetuximab after progression on afatinib in patients with EGFR mutation-positive non-small-cell lung cancer and acquired resistance to gefitinib or erlotinib. (November 2017) - Horn, Leora; Gettinger, Scott; Camidge, D. Ross; Smit, Egbert F.; Janjigian, Yelena Y.; Miller, Vincent A.; Pao, William; Freiwald, Matthias; Fan, Jean; Wang, Bushi; Chand, Vikram K.; Groen, Harry J.M.
Abstract: Objectives: In a phase Ib trial, afatinib plus cetuximab demonstrated promising clinical activity (objective response rate [ORR]: 29%; median progression-free survival [PFS]: 4.7 months) in patients with epidermal growth factor receptor ( EGFR ) mutation-positive non-small-cell lung cancer (NSCLC) with acquired resistance to erlotinib or gefitinib. Here, a separate cohort exploring afatinib plus cetuximab after progression on afatinib is reported. Materials and methods: Patients with EGFR mutation-positive NSCLC who progressed on erlotinib or gefitinib received afatinib 40 mg daily until progression, followed by afatinib daily plus cetuximab 500 mg/m 2 every 2 weeks until progression or intolerable adverse events (AEs). Endpoints included safety, ORR, and PFS. Results: Thirty-seven patients received afatinib monotherapy. Two (5%) patients responded; median PFS was 2.7 months. Thirty-six patients transitioned to afatinib plus cetuximab. Four (11%) patients responded; median PFS was 2.9 months. Median PFS with afatinib plus cetuximab for patients who received afatinib monotherapy for ≥12 versus <12 weeks was 4.9 versus 1.8 months ( p  = 0.0354), and for patients with T790M-positive versus T790M-negative tumors was 4.8 versus 1.8 months ( p  = 0.1306). Fifty percent of patients receiving afatinib plus cetuximab experienced drug-related grade 3/4 AEs. The most frequent drug-related AEs (any grade) were diarrhea (70%), rash (49%), and fatigue (35%) with afatinib monotherapy and rash (69%), paronychia (39%), and dry skin (36%) with afatinib plus cetuximab. Conclusion: Sequential EGFR blockade with afatinib followed by afatinib plus cetuximab had a predictable safety profile and demonstrated modest activity in patients with EGFR mutation-positive NSCLC with resistance to erlotinib or gefitinib. ClinicalTrials.gov identifier: NCT01090011.